2018
DOI: 10.3389/fimmu.2018.02430
|View full text |Cite
|
Sign up to set email alerts
|

Human and Murine Evidence for Mechanisms Driving Autoimmune Photosensitivity

Abstract: Ultraviolet (UV) light is an important environmental trigger for systemic lupus erythematosus (SLE) patients, yet the mechanisms by which UV light impacts disease are not fully known. This review covers evidence in both human and murine systems for the impacts of UV light on DNA damage, apoptosis, autoantigen exposure, cytokine production, inflammatory cell recruitment, and systemic flare induction. In addition, the role of the circadian clock is discussed. Evidence is compared in healthy individuals and SLE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 167 publications
0
29
0
8
Order By: Relevance
“…Low-dose UVB exposure may have an immune-suppressive effect, protecting against autoimmune diseases. Conversely, there are multiple mechanisms that may contribute to acute effects of intense UV exposure on the development of an autoimmune response (28), including increased reactive oxidative species, damage to DNA, and apoptosis leading to cellular debris and other changes; high doses of UVB radiation and sunburn can trigger an immune response to neoantigens, and sunburn itself is an acute inflammatory response to cutaneous damage induced by high UV exposures (28,29). We hypothesized that these types of high-intensity exposures were more relevant to the development of the DM phenotype, whereas lower-level exposures with protective effects might act similarly across multiple phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose UVB exposure may have an immune-suppressive effect, protecting against autoimmune diseases. Conversely, there are multiple mechanisms that may contribute to acute effects of intense UV exposure on the development of an autoimmune response (28), including increased reactive oxidative species, damage to DNA, and apoptosis leading to cellular debris and other changes; high doses of UVB radiation and sunburn can trigger an immune response to neoantigens, and sunburn itself is an acute inflammatory response to cutaneous damage induced by high UV exposures (28,29). We hypothesized that these types of high-intensity exposures were more relevant to the development of the DM phenotype, whereas lower-level exposures with protective effects might act similarly across multiple phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…CLE is found in up to 70% of patients with SLE and can also occur as a skinonly condition (Stannard and Kahlenberg, 2016). In her talk, Dr Kahlenberg outlined recent developments in our understanding of CLE, including inflammatory mediators, differences in lesional subtypes, predisposition to inflammation in normalappearing SLE skin, and mechanisms of flare by UV light (Sarkar et al, 2018;Wolf et al, 2018). These findings have been the driver behind new trials of medications for CLE treatment.…”
Section: Immunopathogenesis Of Complex Skin Diseasesmentioning
confidence: 99%
“…[85,86] Natural killer T (NKT) cells, which share characteristics of natural killer (NK) cells and T cells, represent an effective cell subpopulation in pathogen and tumor cell defense. [87,88] The high number and functionality of NKT cells in blood or tumor was demonstrated to directly correlate with better survival in different human cancers. [88] The advantage of NKT cells over conventional T cells may be their pronounced intrinsic anti-tumor activity through their endogenous TCR [88,89] and is triggered by glycolipids presented via CD1d on antigen-presenting cells.…”
Section: Effec Tiveanti G Entarg E Tingmentioning
confidence: 99%
“…[87,88] The high number and functionality of NKT cells in blood or tumor was demonstrated to directly correlate with better survival in different human cancers. [88] The advantage of NKT cells over conventional T cells may be their pronounced intrinsic anti-tumor activity through their endogenous TCR [88,89] and is triggered by glycolipids presented via CD1d on antigen-presenting cells. [88,89] In a phase 1 trial with melanoma patients, the use of NKT cells was shown to be feasible.…”
Section: Effec Tiveanti G Entarg E Tingmentioning
confidence: 99%
See 1 more Smart Citation